Increase of Carrier-to-Noise Ratio in GPS Receivers Caused by Continuous-Wave Interference - Li, Jian; Nie, Junwei; Li, Baiyu; Wang, Feixue (Společnost pro radioelektronické inženýrství, 2016)
The increased use of personal private devices (PPDs) is drawing greater attention to the effects of continuous-wave interference (CWI) on the performance of global positioning system (GPS) receivers. The effective carrier-to-noise density ratio (C/N0), an essential index of GNSS receiver performance, is studied in this paper. Receiver tracking performance deteriorates in the presence of interference. Hence, the effective C/N0, which measures tracking performance, decreases. However, simulations and bench tests have shown that the effective C/N0 may increase in the presence of CWI. The reason is that a sinusoidal signal is induced by the CWI in the correlator and may be tracked by the carrier tracking loop. Thus, the effective carrier power depends on the power of the signal induced by the CWI, and the effective C/N0 increases with the power of the CWI. The filtering of the CWI in the carrier tracking loop correlator and its effect on the phase locked loop (PLL) tracking performance are analyzed. A mathematical model of the effect of the CWI on the effective C/N0 is derived. Simulation results show that the proposed model is more accurate than existing models, especially when the jam-to-signal ratio (JSR) is greater than 30 dBc.
Keywords: Receiver performance; interference monitoring; signal-to-interference-plus-noise ratio